Star Wars. Smuggler's run : a Han Solo & Chewbacca adventure - Rucka, Greg (Journey to Star Wars: the force awakens, 2015)
"In this story, set between Star Wars: a New Hope and Star Wars: the Empire Strikes Back, Han and Chewie must fly the Millennium Falcon on a top-secret mission for the Rebellion, while evading ruthless bounty hunters and a relentless imperial agent."--Page 4 of cover.